Study on different moduli T-section beams: Pure bending elastic solution and PMMA experiment - Aijun Li (Elsevier, 2021)
In order to accurately analyze the bending problem of T-section beams, a novel analytical method is proposed based on the simplified mechanical model of T-section beams with different tension and compression moduli. Firstly, the expressions of the neutral layer position, normal stress, bending stiffness and displacement of the four-point bending test beam of two types of T-section beams are derived based on the classical beam theory. Then, the expressions of the rectangular section beam are obtained by degenerating the expressions of T-section. Finally, the proposed method is verified via the finite element simulation and the four-point bending test beam of two types of T-section beams with Polymethyl methacrylate (PMMA). From the comparative analysis, the theoretical solutions of the proposed analytical method agree well with the results of the experimental data and the finite element. The flexural modulus can be obtained accurately by the proposed method with the compression and tensile moduli of the beam, which can be used as an efficient and theoretical approach to determine the flexural modulus of the T beam instead of conducting bending experiments.